Academic peer tutors and academic biliteracy development in students of Spanish as a heritage language. (3rd July 2018) - Reznicek-Parrado, Lina M.; Patiño-Vega, Melissa; Colombi, M. Cecilia
ABSTRACT: This study explores the literacy development of students who speak Spanish as a heritage language and who participate in mandatory, peer-to-peer tutoring sessions outside of the classroom. We explore students' academic development as well as their self-positioning as heritage speakers in a bilingual academic setting. Drawing on Systemic Functional Linguistics (SFL), we analyze the written production of seven bilingual students enrolled in a Native Speaker Program at a large, public university. We focus on the development of their academic language through the support of a heritage language tutor and explore the role of the peer tutor as a facilitator in this process. Additionally, we employ Appraisal Theory to analyze interviews in which the same participants explore their bilingual identities and how they position themselves interpersonally as a result of conversations held with a peer mentor, thus demonstrating the benefits of learning Spanish as a heritage language through peer-led learning in academic contexts.